Sulfasalazine exposure during pregnancy and lactation induces alterations in reproductive behavior in adult female rat offspring - Forcato, Simone (2022)
Aims: Sulfasalazine (SAS) is the first line drug in the treatment of chronic inflammatory bowel diseases in pregnant women. SAS and its metabolites cross the placenta and can be transferred through the milk. However, the long-term consequences to the reproductive system of offspring from dams exposed to SAS have not yet been studied. Thus, our study investigated the effects of SAS treatment during gestational and lactational periods on maternal care in F0 and reproductive outcomes in F1 females. Main methods: Wistar female rats (n = 10/group) received 300 mg/kg/day of SAS dissolved in carboxymethyl cellulose (CMC), by gavage, from gestational day 0 to lactation day 21 and 3 mg/kg/day of folic acid during gestation. The control group received CMC only. On PND 21, the female pups were selected for reproductive evaluation at different time points: infancy and adulthood. The reproductive parameters evaluated were installation of puberty (vaginal opening and first estrus), estrous cyclicity, reproductive organs weight, histological analysis of the ovary follicles and uterus, analysis of oxidative stress in ovarian tissue, reproductive behavior (sexual and maternal), and fertility. Key findings: SAS treatment decreased the retrieving behavior in F0 females. The F1 females presented an increase in the lordosis score, frequency of lordosis of magnitude 3, and lipid peroxidation of ovarian tissues in both infancy and adult life. Significance: The SAS effects observed in the current study represent a relevant concern for public health, as they demonstrated that treatment with SAS compromised the maternal motivation of dams and induced reproductive alterations in F1 females.